EVOLUTION OF LOGISTICS MANAGEMENT CONCEPTS IN E-COMMERCE - Nataliia Ilchenko; Olha Freiuk (Izdevnieciba "Baltija Publishing", 2020)
In modern conditions, taking into account the rapid development of Internet technologies, e-commerce increases sales worldwide and has already been formed as a separate sector of the economy. One of the most significant changes that trade is currently undergoing is the progressive development and introduction of a remote way of selling goods. The growing popularity of implementing of the latest sales methods by the trade enterprises requires new approaches to the organization of supply of goods, ensuring their timely delivery and achieving the appropriate level of quality of customer service. In developed countries, logistics is the driving force behind the changes in e-commerce enterprises that have developed significantly over the past 40 years. The precondition for the active development of logistics through the remote sale of goods was the emergence of electronic money in 1980-1990. At the same time, the first logistics companies appeared in the United States, the concept of "outsourcing" was introduced and distribution centers were formed. The change of the traditional paradigm in trade to customer orientation, "pull system", gave impetus to changes in the management system of logistics flows. Thus, in 1992, a new concept of ECR (Efficient Consumer Response - economic relations with customers), which focused primarily on optimizing distribution channels and reducing costs not related to the process of creating valu, appeared. So, as for now, the question about the study of the evolution of logistics management in e-commerce arises. The article investigates the formation of the conceptual foundations of logistics management of the enterprise taking into account the transformation of e-commerce.